Abandoning the Concept of Cultural Ecosystem Services, or Against Natural–Scientific Imperialism. (20th February 2019) - Kirchhoff, Thomas
Abstract: The ecosystem services approach has become highly influential in environmental sciences and policy. However, its concept of cultural ecosystem services (ES)—which is intended to cover the nonmaterial benefits pertaining to nature—exhibits fundamental conceptual flaws. First and foremost, the concept of ecosystem misrepresents the entities to which these benefits refer, which are not natural–scientific entities but categorically different, aesthetic–symbolic phenomena. In addition, the concept of services does not cover the entire spectrum of people's anthropocentric, nonmaterial appreciations of nature. Finally, the attribute cultural, depending on its definition, is either too broad or too narrow to specify all nonmaterial appreciations of nature. These conceptual flaws lead to serious methodological shortcomings, practical errors, and communication problems. To achieve an appropriate conceptual, social, and political assessment of nonmaterial appreciations of nature, these must be addressed outside of an ES approach, via conceptualizations such as nature's aesthetic–symbolic contributions to people.